The Chemistry of Alkali Metals: Properties, Reactions, and Applications (The Peerian Journal, 2023)
This article provides an overview of the chemical properties of alkali metals, including their reactivity, solubility, and unique atomic structures. It could also discuss how these properties make alkali metals useful in a range of applications, from medicine to agriculture.